The Study of Climate Change Factors Affected Quality of Long Kong Production of Farmers in Bang Nara Basin, Narathiwat Province - Thaiburi, Narid; Sinnarong, Nirote (Princess of Naradhiwas University Journal, 2021)
This study aimed to investigate factors affected quality of longkong production due to climate change and adaptations of longkong farmers. This community participatory action research was specifically selected samples of 151 farmers from Bang Nara basin, Narathiwat province. Data including factors affected quality of longkong production, adaptations of longkong farmers, production cost and selling price was analyzed using statistical analysis and logit model. The results showed that the main factors affected quality of longkong production were farmer experience of longkong plantations, impact of average rainfall on production, impact of climate change on length of flower buds, receiving longkong production training and longkong tree age at 12.45, 10.05, 9.15, 7.46, and 7.20%, respectively. The adaptations for improving quality of longkong production are suggested to use of technology and to apply chemicals used; however, these could affect the production cost of longkong farmers.